Finger dexterity and visual discrimination following two yoga breathing practices - Telles, Shirley (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Practicing yoga has been shown to improve motor functions and attention. Though attention is required for fine motor and discrimination tasks, the effect of yoga breathing techniques on fine motor skills and visual discrimination has not been assessed. AIM: To study the effect of yoga breathing techniques on finger dexterity and visual discrimination. MATERIALS AND METHODS: The present study consisted of one hundred and forty subjects who had enrolled for stress management. They were randomly divided into two groups, one group practiced high frequency yoga breathing while the other group practiced breath awareness. High frequency yoga breathing (kapalabhati, breath rate 1.0 Hz) and breath awareness are two yoga practices which improve attention. The immediate effect of high frequency yoga breathing and breath awareness (i) were assessed on the performance on the O′Connor finger dexterity task and (ii) (in) a shape and size discrimination task. RESULTS: There was a significant improvement in the finger dexterity task by 19% after kapalabhati and 9% after breath awareness (P<0.001 in both cases, repeated measures ANOVA and post-hoc analyses). There was a significant reduction (P<0.001) in error (41% after kapalabhati and 21% after breath awareness) as well as time taken to complete the shape and size discrimination test (15% after kapalabhati and 15% after breath awareness; P<0.001) was also observed. CONCLUSION: Both kapalabahati and breath awareness can improve fine motor skills and visual discrimination, with a greater magnitude of change after kapalabhati.